Prediction of the Mechanism of Sodium Butyrate against Radiation-Induced Lung Injury in Non-Small Cell Lung Cancer Based on Network Pharmacology and Molecular Dynamic Simulations - Zhang, Xiao-zhen; Chen, Mao-jian; Fan, Ping-ming; Su, Ting-shi; Liang, Shi-xiong; Jiang, Wei (Frontiers in Oncology, 2022)
Radiation-induced lung injury (RILI) is a severe side effect of radiotherapy for non-small cell lung cancer (NSCLC) and the major hindrance to improving the efficacy of radiotherapy. Previous studies have confirmed that sodium butyrate (NaB) has potent anti-radiation toxicity and extensive anti-inflammatory, immunomodulatory and anti-tumor effects. However, the mechanism of the protected effect of NaB on RILI has not yet been clarified. This study aimed to explore the underlying protected mechanisms of NaB from RILI in NSCLC through network pharmacology, molecular docking, and molecular dynamic simulations. The predictive targets of NaB were obtained from the PharmMapper database and the collection of literature. The target genes of RILI and NSCLC were predicted from OMIM and GeneCards database. The STRING database yield a protein-protein interaction network. The correlations among core target genes, EGFR, PD-L1, immune infiltrates, and chemokines were analyzed using TIMER 2.0, TIMER, and TISIDB databases. The results of GO and KEGG analyses were based on Metscape database. The core target genes and drug were docked by the AutoDock Vina tool and visualized by PyMOL software. GROMACS software was used to perform MDs. The first five core target genes were AKT1, TP53, NOTCH1, SIRT1, and PTEN. The expressions of these five core target genes were significantly associated with EGFR, PD-L1, immune infiltrates, chemokines, and chemokine receptors, respectively. The results from GO analysis revealed that biological processes were focused on the regulation of smooth muscle cell proliferation, oxidative stress, and cell death. Three key KEGG pathways were enriched in the PI3K-Akt signal pathway, p53 signal pathway, and FOXO signal pathway. The docking of NaB with the five core target genes showed affinity and stability. NaB may protect patients against RILI through multiple target genes including AKT1, TP53, NOTCH1, SIRT1, and PTEN, with multiple signaling pathways including PI3K-Akt signaling pathway, p53 signaling pathway, and FOXO signaling pathways involving. Hence, the mechanism of NaB against RILI indicates multi-target and multi-pathway. Our findings effectively provide a feasible theoretical basis for further elucidation of NaB in the treatment of RILI.